Investigation of the bioactivities of Saponaria mesogitana methanolic extract along with its phytochemical composition - Ozay Cennet; Alkac Cerci Burcu; Temel Aybala; Pehlivan Melek (Journal of the Serbian Chemical Society)
Saponaria species are known to contain saponins which have a wide variety of biological activities. But up to now, the phenolic compounds of Saponaria mesogitana have not been clarified. Therefore, this study aimed to determine the phenolic composition and some biological activities of S. mesogitana for the first time. The antioxidant activities of the methanol and water extracts were assessed using the DPPH, FRAP and β-carotene/linoleic acid assays, while the total secondary metabolite content, including phenolics, flavonoids and saponins, was also determined for both extracts. Based on the antioxidant activity and total phenolic and flavonoid contents, further HPLC analysis, as well as anticancer and antimicrobial activity experiments, were conducted using the methanol extract. The anticancer potential was assessed using the MTT assay and wound healing migration test, while antibacterial activity was evaluated through disc diffusion and MIC assays. Additionally, the antibiofilm properties of the extract were examined using the crystal violet method. The methanolic extract showed high antioxidant activity, while caffeic acid and epicatechin were characterized as major phenolic compounds by HPLC. S. mesogitana inhibited not only bacterial growth but also the levels of migration of SHSY-5Y cancer cells. These findings indicate that S. mesogitana possesses potent antioxidant, anticancer, antimicrobial and antibiofilm activities associated with its bioactive phenolic constituents.